Modulation of the Gut Microbiota and Liver Transcriptome by Red Yeast Rice and Monascus Pigment Fermented by Purple Monascus SHM1105 in Rats Fed with a High-Fat Diet - Yang, Hua; Pan, Ronghua; Wang, Jing; Zheng, Lizhong; Li, Zhenjing; Guo, Qingbin; Wang, Changlu (Frontiers in Pharmacology, 2021)
Hyperlipidemia can easily cause atherosclerosis, induce cardiovascular and cerebrovascular diseases. Red yeast rice contains a variety of active ingredients and is a commonly used food with the same medicine and food, and has pharmacological effects such as lowering blood lipids. In this study, we select Monascus strains SHM1105 with high yield of Monacolin K and monascus pigment, and studied the effects of the red yeast rice (RYR) and monascus pigment (PIG) fermented by this strain on the changes of blood lipids, intestinal flora and liver transcriptome in hyperlipidemia model rats. The experimental results show that compared with the high-fat model group, the weight growth rate, liver weight ratio, kidney weight ratio, spleen weight ratio, and fat weight ratio of rats in the gavage lovastatin (LOV), RYR and PIG group were all significant decrease (P<0.05). After the intervention of red yeast rice and monascus pigment, it can significantly reduce the serum TC, TG and LDL-C levels, which has the effect of lowering blood lipids. The 16SrDNA sequencing results showed that the ratio of Firmicutes/Bacteroidetes decreased significantly (P≤0.01) after the intervention of LOV, RYR and PIG; The abundance of the ratio of Lachnospiraceae, Ruminococcaceae, Prevotellaceae and Bacteroidales-S24-7-group has also changed. The combined analysis of transcriptome and metabolome showed that lovastatin, red yeast rice and monascus pigment can all improve lipid metabolism in rats by regulating Steroid hormone biosynthesis, Glycerolipid metabolism and Arachidonic acid metabolism pathway. In addition, RYR and PIG also has a unique way of regulating blood lipids. Although a lot of research on the lipid-lowering components of Monascus rice and the single pigment component of Monascus has been carried out, the actual application is RYR and pigments as mixtures. As a mixture of RYR and PIG contains a variety of biologically active ingredients, and each component may have a synergistic effect. Therefore, it has a lipid-lowering mechanism that lovastatin does not have. Therefore, red yeast rice and monascus pigment are effective in reducing lipid Potential development and utilization in functional foods.